HISTOLOGICAL EFFECTS OF AQUEOUS EXTRACT OF Mentha spicata ON LIVER IN ALBINO MICE - H. Ali, L. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to investigate the effects of high concentration of Mentha spicata on liver tissues. Fourteen mature male albino mice were used in this study and divided into two groups. Control group received 1 ml normal saline daily for 7days through oro- gastric tube. The remained animals received 1ml of aqueous extract of Mentha spicata daily for 7 days through oro-gastric tube. At the end of experiment, all animals were dissected. Liver Samples were fixed in 10% buffered formalin and embedded in paraffin. Sections were prepared and stained with hematoxylin and eosin. The slides were examined macroscopically. The results showed that coagulative degeneration, degeneration of hepatocytes with necrosis, inflammation vacuolization, inflammatory cell infiltration and fatty degenerative changes as also hemorrhage and increased size of Kupffer cells and vacuolated cytoplasm. From this study it has been concluded that high concentration of aqueous extract of Mentha spicata have a side effect on the structure and function of liver tissue.